Benny and Penny in Lights out! : a Toon book - Hayes, Geoffrey (New York : Toon Books, 2012)
At bedtime two mouse siblings take turns telling stories and calming night fears.
Keywords: Graphic novels; Bedtime -- Fiction; Brothers and sisters -- Fiction; Mice -- Fiction; Graphic novels